Can lenalidomide play a role in the management of scleritis?. (18th June 2013) - Al-Jafar, Hassan A; Abul, Nadia; Kumar, Niranjan; Al-Awadhi, Adel
Abstract : Lenalidomide is an immunomodulatory agent that was approved for the treatment of a monoclonal bone marrow disorders, myelodysplastic syndrome del(5q)(MDS del(5q)), in 2005; the drug was subsequently also approved for the treatment of refractory multiple myeloma, a bone marrow malignancy of the B-lymphocyte lineage. The purpose of this study is to report a case of MDS del(5q) in a female patient, which was most likely secondary to the immunosuppressive drugs that the patient was taking for scleritis. After lenalidomide treatment, the patient's haematological symptoms rapidly resolved and she became transfusion independent, with normal haemoglobin levels. This medication also helped control her dependence on high doses of oral prednisolone. The patient continued to receive treatment with low-dose lenalidomide, and her scleritis has been in long-term remission for 3 years. A larger prospective study can further define the role of lenalidomide in the management of scleritis.